MENGUAK KEKUATAN LIDIMATIKA DALAM KONTEKS PEMBELAJARAN: PENDEKATAN NEUROSCIENCE - Fitriasari, Fitriasari; Fadillah, Ilah; Leksono, Suroso Mukti; Agam, Ihfa Nur (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2024)
Mathematics learning aims to develop students' abilities in solving problems. Mathematics learning is expected to provide students with experience, both in solving mathematical problems and everyday life problems. This article aims to reveal the power of lidimatics, an innovation in mathematics learning using sticks with a qualitative approach using literature studies and a neuroscience approach. By analyzing the results of previous research contained in the article search engine or Google Scholar. With linguistic media, students can easily understand the concept of multiplication through direct experience, reducing the need for memorization and increasing their understanding. As an effective alternative, the linguistic multiplication method illustrates that a creative approach can help students overcome mathematical difficulties better. Through a neuroscience approach in learning mathematics, it provides deep insight into the cognitive processes involved in learning mathematics.